2021
DOI: 10.3390/met11091451
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of PdCuRu Porous Nanoplates as Highly Efficient Electrocatalysts for Hydrogen Evolution Reaction in Alkaline Medium

Abstract: Ru is a key component of electrocatalysts for hydrogen evolution reaction (HER), especially in alkaline media. However, the catalytic activity and durability of Ru-based HER electrocatalysts are still far from satisfactory. Here we report a solvothermal approach for the synthesis of PdCuRu porous nanoplates with different Ru compositions by using Pd nanoplates as the seeds. The PdCuRu porous nanoplates were formed through underpotential deposition (UPD) of Cu on Pd, followed by alloying Cu with Pd through inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Alloy nanosheets with more than two metal elements can be prepared using the strategies discussed above. PdPtNi trimetallic nanosheets were synthesized by a solution-phase method using a Pd nanosheet as template Figure a and b show the TEM images for the as-prepared PdPtNi nanosheets.…”
Section: Materials Developments Of 2d Metal Nanosheetsmentioning
confidence: 99%
“…Alloy nanosheets with more than two metal elements can be prepared using the strategies discussed above. PdPtNi trimetallic nanosheets were synthesized by a solution-phase method using a Pd nanosheet as template Figure a and b show the TEM images for the as-prepared PdPtNi nanosheets.…”
Section: Materials Developments Of 2d Metal Nanosheetsmentioning
confidence: 99%
“…Recently, the synthesis of multimetallic Ru-based composite has become a hot topic in recent decades because of its numerous significant applications. Due to an electronic effect and multiple synergetic effects and increasing the surface area, multicomponent metallic NPs often show more unique catalytic active sites and high current responses, etc . Ru-based bi/multimetallic NPs have improved catalytic selectivity/activity, high stability, and great efficiency when compared to monometallic NPs. Recently, for instance, Kivrak et al reported the synthesis of multimetallic Ru–Mo–Pd/MWCNT/GCE electrode as an enhanced EC sensitive detection of l -cysteine ( l -Cys) sensor. In fact, the EC behavior of Ru/MWCNT/GCE was superior to that of Ru–Mo–Pd/MWCNT/GCE, which showed an LOD of 0.1 μM, WLR of 5–200 μM, and with a sensitivity of 0.136 μA –1 μM –1 in the presence of l -Cys.…”
Section: Introductionmentioning
confidence: 99%